The Swedish Pregnancy Register – for quality of care improvement and research. (14th December 2017) - Stephansson, Olof; Petersson, Kerstin; Björk, Camilla; Conner, Peter; Wikström, Anna‐Karin
Abstract: Introduction: The objective of this study was to present the Swedish Pregnancy Register and to explore regional differences in maternal characteristics, antenatal care, first trimester combined screening and delivery outcomes in Sweden. Material and methods: The Pregnancy Register (www.graviditetsregistret.se ) collects data on pregnancy and childbirth, starting at the first visit to antenatal care and ending at the follow‐up visit to the antenatal care, which usually occurs at around 8–16 weeks postpartum. The majority of data is collected directly from the electronic medical records. The Register includes demographic, reproductive and maternal health data, as well information on prenatal diagnostics, and pregnancy outcome for the mother and the newborn. Results: Today the Register covers more than 90% of all deliveries in Sweden, with the aim to include all deliveries within 2018. The care providers can visualize quality measures over time and compare results with other clinics, regionally and nationally by creating reports on an aggregated level or using case‐mix adjusted Dash Boards in real time. Detailed data can be extracted after ethical approval for research. In this report, we showed regional differences in patient characteristics, antenatal care, fetal diagnosis and delivery outcomes in Sweden. Conclusions: Our report indicates that quality in antenatal and delivery care in Sweden varies between regions, which warrants further actions. The Swedish Pregnancy Register is a new and valuable resource for benchmarking, quality improvement and research in pregnancy, fetal diagnosis and delivery.